Feasibility Test of Moocs Platform Development for Interactive Adaptive Digital Modules for Hybrid Classes Implementation in Providing Easy Access for Students with Disabilities - Fitranita, Vika; Risdianto, Eko; Ardina, Mona (CV Media Inti Teknologi, 2024)
This article aims to present the results related to the feasibility test of the moocs platform for interactive adaptive digital modules for the implementation of hybrid classes in providing easy access for students with disabilities that have been developed. The research was conducted in 2024 by 3 researchers. Researchers developed the product by applying the ADDIE model (Analysis, Design, Develop, Implementation, Evaluation). One of the processes of the development model is to conduct a feasibility test on the product being developed. The feasibility test was carried out by 4 validators by filling out a closed questionnaire. The aspects that were the focus of the assessment by the validators were the Graphics Aspect, Media Aspect, Language Feasibility Aspect, Presentation Feasibility Aspect, and Content Feasibility Aspect. The feasibility test of the developed product was carried out by 4 validators with the focus of the assessment being the Graphics Aspect, Media Aspect, Language Feasibility Aspect, Presentation Feasibility Aspect, and Content Feasibility Aspect. In the four aspects that were the focus of the assessment by the validators, the percentage value obtained was above 85%. So, it can be concluded that the product being developed is feasible to be implemented.